Malapportionment and democracy: A curvilinear relationship. (October 2017) - Ong, Kian-Ming; Kasuya, Yuko; Mori, Kota
Abstract: This article examines electoral malapportionment by illuminating the relationship between malapportionment level and democracy. Although a seminal study rejects this relationship, we argue that a logical and empirically significant relationship exists, which is curvilinear and is based on a framework focusing on incumbent politicians' incentives and the constraints they face regarding malapportionment. Malapportionment is lowest in established democracies and electoral authoritarian regimes with an overwhelmingly strong incumbent; it is relatively high in new democracies and authoritarian regimes with robust opposition forces. The seminal study's null finding is due to the mismatch between theoretical mechanisms and choice of democracy indices. Employing an original cross-national dataset, we conduct regression analyses; the results support our claims. Furthermore, on controlling the degree of democracy, the single-member district system's effects become insignificant. Australia, Belarus, the Gambia, Japan, Malaysia, Tunisia, and the United States illustrate the political logic underlying curvilinear relations at democracy's various levels. Highlights: A curvilinear relationship between malapportionment and democracy levels is shown. Provides an original data set of lower chamber malapportionment for 160 countries. A controlled level of democracy turns single-member district system insignificant.